1975
DOI: 10.1515/bchm2.1975.356.1.425
|View full text |Cite
|
Sign up to set email alerts
|

Imcorporation of Orotic Acid into Nucteotides and RNA in Mouse Organs during 60 Minutes

Abstract: Mouse kidney and liver were found to increase their levels of radioactivity above that of serum from 2 to 60 min after administration of [6-14 C]orotic acid. In spleen, thymus and brain, the radioactivity level reached a maximum soon after the injection and then decreased, as did that in serum. Sixty minutes after the injection, 44% of the administered isotope dose was found in the kidneys, 22 % in the liver and 0.75% in the spleen. The 14 C activity in liver UTP increased rapidly and then remained constant fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Orotate (orotic acid, 6-carboxyuracil), a normal intermediate in pyrimidine metabolism, is converted to uridine 5 0 -triphosphate (UTP), which is utilized for the synthesis of RNA and for the synthesis of uridine 5 0 -diphosphohexoses and uridine 5 0 -diphosphohexosamines (UDP sugars) [1][2][3]. Since UDP sugars are used in the glycosylation of the basement membrane collagen, increased bioavailability of these compounds is involved in the pathogenesis of renal hypertrophy with concomitant thickening of the glomerular and tubular basement membranes observed in human diabetes mellitus [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Orotate (orotic acid, 6-carboxyuracil), a normal intermediate in pyrimidine metabolism, is converted to uridine 5 0 -triphosphate (UTP), which is utilized for the synthesis of RNA and for the synthesis of uridine 5 0 -diphosphohexoses and uridine 5 0 -diphosphohexosamines (UDP sugars) [1][2][3]. Since UDP sugars are used in the glycosylation of the basement membrane collagen, increased bioavailability of these compounds is involved in the pathogenesis of renal hypertrophy with concomitant thickening of the glomerular and tubular basement membranes observed in human diabetes mellitus [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown by biochemical method that RNA in various tissues may be derived from labeled uridine (22)(23)(24)(25)(26)(27)(28) and labeled orotic acid (22,23,29,30) . In the small intestine of the rat, however, Raisonnier et al (31) reported incorporation of ['°C]uridine, but of only traces of [ t 'C]orotic acid, which implies that orotic acid was not a suitable precursor for studies of RNA in rat small intestine .…”
mentioning
confidence: 99%
“…Orotic acid has been actively utilized for the synthesis of pyrimidine nucleotides in the liver and kidney of rats [15,16]. Other organs characterized by rapid nucleic acid synthesis…”
Section: Resultsmentioning
confidence: 99%
“…Orotic acid has been actively utilized for the synthesis of pyrimidine nucleotides in the liver and kidney of rats [15,16]. Other organs characterized by rapid nucleic acid synthesis expt (a) 8.1 x lo6 counts/min and in expt (b) 12.3 x lo6 counts/min of [2-'4C]orotic acid was injected per The specific activity of DNA cytosine and thymine on the 11th and 14th day after the administration of [2-'4C]orotic acid is higher than the specific activity of the pyrimidine components of DNA on the 6th day after the administration of the labeled precursor.…”
Section: Resultsmentioning
confidence: 99%